Structural Efficiency and Embodied Carbon Assessment of Pre-Engineered Versus Conventional Steel Beams - Suwondo, Riza; Suangga, Made; Keintjem, Militia; Alzhrani, Traad (Journal of Engineering and Sustainable Development, 2026)
The increased focus on the reduction of greenhouse gas emissions in the building and construction sector has heightened the demand for structural systems that reduce both material and embodied carbon. Pre-engineered building (PEB) systems using tapered built-up steel beams could potentially offer a viable alternative to traditional hot-rolled prismatic sections by better matching and aligning the sectional capacity and the bending demand. However, there are still a limited number of studies that perform comparative analyses integrating structural and environmental impact. This study assessed the structural efficiency and embodied carbon of pre-engineered and conventional steel beams over spans of 6 to 20 m for fixed-end and pinned-end boundary conditions. Structural design was performed in accordance with AISC 360-16, and embodied carbon was assessed for life cycle modules A1–A5 following BS EN 15978. The results indicate that tapered built-up beams achieve higher utilisation ratios and smaller effective section sizes, particularly for short and intermediate spans. Life-cycle assessment shows that pre-engineered beams reduce embodied carbon by approximately 10–25% compared with conventional beams, primarily owing to their lower steel mass. These findings demonstrate that tapered built-up beams offer both structural and environmental advantages in the investigated design context.